The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmicb.2021.689527
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Secondary Metabolites Produced by the Fungal Endophytes: Chemical Diversity and Potential Use in the Development of Biopesticides

Abstract: Plant diseases caused by phytopathogenic fungi can lead to huge losses in the agricultural fields and therefore remain a continuous threat to the global food security. Chemical-based fungicides contributed significantly in securing crop production. However, indiscriminate application of fungicides has led to increased chemical resistance and potential risks to human health and environment. Thus, there is an urgent need for searching for new bioactive natural products and developing them into new biopesticides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…niveum, Fusarium oxysporum f. sp. vasinfectum, and Gibberella saubinettii), with MIC values of 13.7-100 μM, which were comparable to the positive controls (Xu et al, 2021).…”
Section: Antifungal Activitymentioning
confidence: 53%
“…niveum, Fusarium oxysporum f. sp. vasinfectum, and Gibberella saubinettii), with MIC values of 13.7-100 μM, which were comparable to the positive controls (Xu et al, 2021).…”
Section: Antifungal Activitymentioning
confidence: 53%
“…Within the wide range of secondary metabolites produced by fungi, especially fungal endophytes, many of them have antimicrobial properties, as described in detail by Mousa and Raizada [ 73 ]. Among those antimicrobial metabolites, a thorough review carried out by Xu et al [ 94 ] showed their wide chemical diversity, with a total of 132 chemical structures being found with antifungal properties, when analyzed over the past two decades. From the compounds included in the present review, most of them (53%) are included within the polyketide compounds ( Figure 1 ).…”
Section: Secondary Metabolites Of Fungi With Antifungal Propertiesmentioning
confidence: 99%
“…Endophytic fungi from medicinal plants are known for their ability to produce a variety of bioactive natural products with novel skeletons [1][2][3][4]. Their secondary metabolites, such as alkaloids, terpenoids and polyketides, possess antibacterial, cytotoxic, antiinflammatory, antidiabetic and other biological activities [5][6][7].…”
Section: Introductionmentioning
confidence: 99%